LEADERSHIP CONCEPT ANALYSIS STUDY IN ISLAMIC PERSPECTIVE - Hilmi Qosim Mubah; Erny Roesminingsih; Badrus Soleh; Kacung Wahyudi; Haris Supratno (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2024)
Leadership in Islam does not emerge from the imagination of its adherents but is summarized in the Quran and the hadith of the Prophet Muhammad SAW. This study aims to describe Leadership in an Islamic Perspective, Basic Foundations of Islamic Leadership, Normative Foundations of Islamic Leadership, Essential Principles of Leadership in Islam, and the Prophetic Leadership Paradigm. This study uses the Systematic Literature Review (SLR) method with the PRISMA model, a series of evidence-based minimums to assist in reporting systematic reviews and meta-analyses. The results of the study indicate that Islamic leadership is a leadership concept based on the example of the Prophet Muhammad SAW who balances success in various aspects of life. Based on the Quran and Hadith, Islamic leadership is based on the principles of monotheism, equality, Islamic unity, deliberation, justice, and welfare. An Islamic leader must uphold the principles of trust, fairness, shura, and amr bi al-ma'ruf wa nahy 'an al-munkar, aimed at influencing other people to sincerely follow instructions as a reflection of obedience to Allah SWT.